0391 Heart rate variability in particle exposed train drivers in the Stockholm subway. (23rd June 2014) - Bigert, Carolina; Alderling, Magnus; Svartengren, Magnus; Plato, Nils; Anderson, Martin; Wiklund, Andreas; Gustavsson, Per
Abstract : Objectives: Exposure to particulate matter in urban air is a recognised risk factor for cardiovascular disease, but little is known about possible effects from exposure to the high levels of metal-rich particles prevailing in underground subway systems. This led us to investigate heart rate variability (HRV) in occupationally exposed subway drivers. Method: 29 train drivers (18 men and 11 women) in the Stockholm subway were investigated from November 2004 to March 2005. All were non-smokers in ages 25–50. Personal particle exposure levels were obtained in an occupational hygienic investigation (mean PM2.5 19 µg/m 3, DataRAM 33 µg/m 3 ). We registered continuous ECG over 24 h. The HRV measures obtained were LF, HF, LF/HF, HR and SDNN. The arithmetic mean (based on 5-minutes intervals) in the group was calculated for each measure and exposure situation, as well as the mean in group of the individual quotients between the exposure situations. One-sample t-tests were used to analyse whether the quotients differed from one. Results: The mean quotients between working in tunnel and working outside tunnel were significantly above one for LF (p = 0.04) and significantly below one for HR (p = 0.03) and SDNN (p = 0.00). The quotients between total working-hours and leisure-hours were significantly above one for HR (p = 0.03) and significantly below one for SDNN (p = 0.00). Conclusions: Overall, our results do not indicate any clinically significant effects on the cardiac autonomic function, as measured by HRV, for particle exposed subway drivers in Stockholm, even though there were some indications of a decrease in SDNN.